IMPLEMENTASI REINFORCEMENT POSITIF DALAM MENINGKATKAN KUALITAS BELAJAR SISWA BROKEN HOME KELAS IV SD ISLAM COKROAMINOTO - Wulandari, Wulandari; Baihaqi, Mohammad (Cahaya Ilmu Bangsa Institute, 2025)
This descriptive qualitative research examines the application of positive reinforcement to improve the learning quality of broken home students at the Cokroaminoto Islamic Elementary School, Balikpapan. This research aims to understand how positive reinforcement is applied and identify supporting and inhibiting factors. Data was collected through classroom observations, interviews with teachers and students, as well as documentation studies. Observed positive reinforcement included verbal praise, applause, and physical contact such as a handshake. The research results show a significant positive impact from implementing positive reinforcement. Having aspirations, sufficient student interest in learning, varied learning methods and student motivation are supporting factors for success. Meanwhile, broken home backgrounds and differences in student characteristics become obstacles. Penelitian kualitatif deskriptif ini mengkaji penerapan reinforcement positif untuk meningkatkan kualitas belajar siswa broken home di Sekolah Dasar Islam Cokroaminoto, Balikpapan. Penelitian ini bertujuan untuk memahami bagaimana reinforcement positif diterapkan dan mengidentifikasi faktor pendukung serta penghambatnya. Data dikumpulkan melalui observasi kelas, wawancara dengan guru dan siswa, serta studi dokumentasi. Reinforcement positif yang diamati meliputi pujian verbal, tepuk tangan, dan kontak fisik seperti jabat tangan. Hasil penelitian menunjukkan dampak positif yang signifikan dari penerapan reinforcement positif. Mempunyai cita-cita, minat belajar siswa yang cukup metode pembelajaran yang bervariatif dan motivasi siswa menjadi faktor pendukung keberhasilan. Sementara itu, latar belakang broken home dan perbedaan karakteristik siswa menjadi penghambat.